Analisis Komparasi Metode CAPM dan APT dalam Memprediksi Return Saham LQ45 2019-2021 - Hartono, Pierdijono; Nugraha, Nugraha; Heryana, Toni; Medidjati, R. Adam (Image : Jurnal Riset Manajemen, 2023)
The investment climate is developing rapidly in Indonesia, many people are interested in investing, and the capital market is a common and legal place to invest. In investing, stocks are one of the long-term financial instruments traded on the capital market. The goal of investors in stock investment is to obtain the maximum stock return with a certain risk. Financial experts have developed two approaches to predict return on investment based on risk and use certain macroeconomic variables, the Capital Asset Pricing Model (CAPM) and the Arbitrage Pricing Theory (APT). This study aims to determine the best model between the CAPM and APT in determining the expected return on shares of companies that are members of the IDX LQ45 for the period 2019-2021. Data is processed using Unbalance Data Panel Analysis with the Eviews application. The results of data processing show that the CAPM method is more precise or accurate than the APT method.